Vector-Borne Disease Intelligence: Strategies to Deal with Disease Burden and Threats - Braks, Marieta; Medlock, Jolyon M.; Hubalek, Zdenek; Hjertqvist, Marika; Perrin, Yvon; Lancelot, Renaud; Duchyene, Els; Hendrickx, Guy; Stroo, Arjan; Heyman, Paul; Sprong, Hein (Frontiers in Public Health, 2014)
Owing to the complex nature of vector-borne diseases, whereby monitoring of human case patients does not suffice, public health authorities experience challenges in surveillance and control of vector-borne diseases. Knowledge on the presence and distribution of vectors and the pathogens they transmit is vital to a risk assessment process to permit effective early warning, surveillance and control of vector-borne diseases. Upon accepting this reality, public health authorities face the phenomenon of an exponential rise in the number of possible surveillance targets and how to decide which are essential. Here, . we propose a comprehensive approach that integrates three surveillance strategies: population-based surveillance, disease-based surveillance and context-based surveillance for EU member states to tailor the best surveillance strategy for control of vector-borne diseases in their geographic region. By classifying the surveillance structure into 5 different contexts, we hope to provide guidance in optimizing surveillance efforts. Contextual surveillance strategies for vector-borne diseases entail combining organization and data collection approaches that result in disease intelligence rather than a preset static structure.